If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36b + -3 = 0 Reorder the terms: -3 + 36b = 0 Solving -3 + 36b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 36b = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 36b = 0 + 3 36b = 0 + 3 Combine like terms: 0 + 3 = 3 36b = 3 Divide each side by '36'. b = 0.08333333333 Simplifying b = 0.08333333333
| (x+3)(x+10)=0 | | 4(1-3n)-14=4(2n+3)-9 | | 2(2y-3)=y-6 | | 6(5-4h)=3(4h-2)-7(6+8h) | | 5x+6+3x-10=180 | | 8a+7(-1-7a)=7(a+7)-8 | | 5v-34=36 | | 4(3m-4)=2m+6 | | 136*0.1= | | -1/2-7=-11 | | 7x+4x=110 | | 8+f-2=-12 | | 8d-d+3d+6=4d | | 155*-0.0155= | | 4(6y-9)+7= | | 3(x-5)=2x+5+3x | | 5c+1=7c-14-2c | | -2k+3=14 | | -30=-2x | | 5x=4x+24 | | 2x+(-5)=8x+1 | | 72x^2-23x-35=0 | | 4x-4=7x-16 | | x^2+2x+1=6x-7-1 | | 4x+139+(2x+29)=180 | | 4(7z-9)-7(4z+3)=6(9z-10) | | -5n+8n=3(8+6n)+6(1-5n) | | 2(9X-4)-7+3(6-5X)=18 | | z=(x+y)w | | 2u+15=55 | | a=0.5bcd+bc | | 7(1-q)=-3(5+3)q |